(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
This paper analyses Euxitheus’ legal arguments in the trial against Eubulides (Dem. 57) and proposes a new analysis of the ephesis procedure. Within this framework it argues that Euxitheus’ forensic strategy is not only relevant to the question at issue – to prove his status as a legitimate citizen (gnesios polites), as someone born from two citizen parents – but is also characterised by a strict adherence to the laws and procedure involving his case. The relation between rhetoric and law emerging in Euxitheus’ speech reveals a rhetorical strategy grounded on legal evidence and documents. This essay will especially focus on two important arguments in the speech, that is, the use of religious arguments and the theme of the plot against Euxitheus, which prove extremely enlightening in showing the how the relevant procedure shaped Euxitheus’ arguments. To this aim section II compares Dem. 57 and other probable cases of ephesis in order to reassess how the ephesis procedure worked when it arose from a diapsephisis. Section III shows that the arguments used by Euxitheus are to be considered relevant to winning an ephesis case in court. The entire speech is effectively constructed to demonstrate ‘what is true’ against Eubulides’ ‘false accusations’ and ‘defamatory statements’ (57.1), that is, to use legal arguments against ‘the sykophant’s game’: to allege everything but prove nothing’.